A Network Analysis of the Associations Between Posttraumatic Stress Symptoms and Posttraumatic Growth Among Disaster‐Exposed Chinese Young Adults. Issue 4 (12th April 2021) - Yuan, Guangzhe; Park, Crystal L.; Birkeland, Samuel R.; Yip, Paul S. Y.; Hall, Brian J.
Abstract: Posttraumatic stress symptoms (PTSS) and posttraumatic growth (PTG) have been shown to coexist following exposure to a traumatic event, but consensus about what accounts for this association is lacking. Network analysis is a novel analytic method that can explain this linkage. In a sample of 1, 809 Chinese college students (66.1% female, age range: 16–35 years) who were directly exposed to a typhoon, we investigated the network structure of PTSS and PTG, along with bridge symptoms and elements, to elucidate how distress and growth coexist. The seven strongest edges found in the model included two between elements in the PTSS cluster, one between elements of PTG, and four between elements of PTSS and PTG. Eight bridge symptoms and elements emerged: intrusive thoughts, emotional cue reactivity, hypervigilance, self‐destructive or reckless behavior, nightmares, and physiological cue reactivity among PTSS, and changed priorities and stronger religious faith among PTG elements. These findings reveal connections between PTSS and PTG that explain how these constructs may coexist in individuals exposed to natural disasters. The network perspective provides a novel way to conceptualize the association between PTSS and PTG and contributes to the field's understanding of recovery after traumatic events.